CONTAR O CORPO: QUANDO O SUBALTERNO ASSUME A NARRATIVA. - Martins, Josiane Aparecida (2012)
The aim of this work is to analyze the novels: Paixao Pagu – early autobiography of Patricia Galvao, by Patricia Galvao, memorial telling of one of the most expressive Brazilian women, directed to Geraldo Ferraz, her intellectual partner and affair; and O Doce Veneno do Escorpiao – o Diario de uma garota de programa, by Bruna Surfistinha, published as the journal of one of the most required prostitutes in Brazil (both published in 2005, but written in different times). Our goal is to follow the track of the subordinate, when it finds the way to make himself listened by the society. In this context we privilege the subject woman because of the silent condition that woman is often submitted. The way followed by this work is going to be done from the theory of writing about self, by Michel Foucault, from the process of deconstruction and deterritorialization, by Gilles Deleuze and Felix Guatarri, and from the studies about autobiography, by Pillippe Lejeune, by the discourse analysis on both authors: Patricia Galvào and Bruna Surfistinha.